Case Report: Pediatric Renal Sarcoidosis and Prognostic Factors in Reviewed Cases - Klaus, Richard; Jansson, Annette Friederike; Griese, Matthias; Seeman, Tomas; Amann, Kerstin; Lange-Sperandio, Bärbel (Frontiers in Pediatrics, 2021)
Background: Pediatric sarcoidosis is a complex inflammatory disorder with multisystemic manifestations. Kidney involvement in children is rare and prognostic factors are unknown. Case report and methods: We report the case of a 16-year-old girl with multi-organ sarcoidosis and renal involvement. The patient presented with tubulointerstitial nephritis (TIN), acute kidney injury (AKI), chest CT disseminated noduli, granulomatous iridocyclitis, giant-cell sialadenitis and arthralgia. The kidney biopsy revealed non-granulomatous interstitial nephritis. Treatment consisted of initial high-dose methylprednisolone-pulse followed by oral prednisolone and methotrexate. Full remission was achieved. In addition, we performed a literature review using PubMed and analysed data on pediatric renal sarcoidosis cases. Results: We identified 36 cases of sarcoidosis with renal involvement on presentation and data on the end-of-follow-up glomerular filtration rate (GFR). The data from the literature review showed that renal involvement was slightly more prevalent in males (60%). Acute kidney injury (AKI) was present in most of the described patients (84%). Only 1 patient improved without therapy. Oral prednisolone was used in every case, in more severe cases other immunosuppressants were used. We newly identified renal concentration impairment and granulomatous interstitial nephritis (GIN) as factors with a clear tendency towards a decreased GFR at the end-of-follow up, emphasizing the importance of kidney biopsy in symptomatic patients. In contrast, higher GFR at presentation and hypercalcemia were rather beneficial factors. According to the identified predictive factors our patient has a good prognosis and is in renal and extrarenal remission. Conclusion: The factors indicating a tendency towards an unfavourable renal outcome in pediatric sarcoidosis are be renal concentration impairment and granulomatous interstitial nephritis at presentation while a higher GFR is beneficial.